Pengaruh Kemanfaatan, Risiko, Kepercayaan, dan Kemudahan Terhadap Minat Pengguna Uang Elektronik - Susanti, Hevi; Saputra, Agung Joni (Universitas Muhammadiyah Metro, 2022)
This research aims to examine the influence of usefulness, risk, trust, and perceived ease of use on interest in using electronic money. The population in this research is the people of Batam City who use electronic money in Batam City. The sample in this study amounted to 180 respondents. perceived usefulness, perceived risk, trust and convenience influence interest in using electronic money by showing the sig value. F (Statistics) of 0.000 is smaller than the significance level of 0.05 and the calculated F value is > from F table, namely 70,384 > 2.42. usefulness influences interest in using electronic money, risk influences interest in using electronic money, trust influences interest in using electronic money, and convenience influences interest in using electronic money, perceived usefulness, perceived risk, trust and perceived ease simultaneously influence interest in using electronic money in Batam City .